Pesan Dakwah dalam "Buku Tuhan Ada Di Hatimu" Karya Habib Husein Ja’far Al-Hadar - Fajar Sidik Nur Fadillah; Ida Afidah; N. Sausan M. Sholeh (Bandung Conference Series: Islamic Broadcast Communication, 2023)
Abstract. In this research, the object of research is the book God Is in Your Heart by Habib Husein Ja'far Al-Hadar. The development of technology has had both positive and negative impacts. The positive is that it facilitates activities, the negative is that it easily erodes religious values. One of the products of science and technology is a book. In circulating the book, it has not been able to answer religious issues. So the book God Is in Your Heart by Habib Husein Ja'far Al-Hadar is one of the answers to minimize the recent religious problems. The purpose of this research is to find out the synopsis and message of da'wah in the book. This research is a type of qualitative research. And the methodology used in this study is content analysis, namely a research technique to obtain an overview of the contents of the da'wah messages in the book. The synopsis in the book is about problems that occur in society. Such as not presenting God in every action, the phenomenon of the trend of "hijrah" which is only limited to mere existence, how to be a wise Muslim, knowledge about morality which is fully regulated in Islam, and also addressing differences and focusing on each individual to be more productive. And also the messages contained in the sub-categories (aqidah, shari'ah, and morals) are faith in Allah, faith in the Prophet, faith in the Book, worship, muamalah, morals to others, and morals to the environment. Abstrak. Dalam penelitian ini objek penelitiannya ialah buku Tuhan Ada di Hatimu karya Habib Husein Ja’far Al-Hadar. Dalam perkembangan ilmu teknologi, ternyata berdampak positif maupun negatif. Positifnya ialah memudahkan aktivitas, negatifnya ialah mudah mengikisnya nilai-nilai agama. Salah satu produk ilmu teknologi ialah buku. Dalam beredarnya buku, belum mampu menjawab persoalan keagamaan. Maka buku Tuhan Ada di Hatimu karya Habib Husein Ja’far Al-Hadar merupakan salah satu jawaban untuk meminimalisir dari permasalahan agama yang terjadi terbaru ini. Tujuan dari penelitian kali ini ialah untuk mengetahui sinopsis dan pesan dakwah dalam buku tersebut. Penelitian kali ini merupakan jenis penelitian kualitatif. Dan metodologi yang digunakan dalam penelitian ini adalah analisis isi yakni teknik penelitian untuk memperoleh gambaran isi pesan dakwah dalam buku tersebut. Sinopsis dalam buku tersebut ialah seputar problem yang terjadi di masyarakat. Seperti tidak menghadirkan Tuhan dalam setiap tindakan, fenomena trend “hijrah” yang hanya sebatas eksistensi belaka, bagaimana menjadi muslim yang bijak, pengetahuan seputar akhlak yang diatur sepenuhnya dalam Islam, dan juga menyikapi sesuatu perbedaan dan berfokus kepada setiap individu agar semakin produktif. Dan juga pesan yang terkandung dalam sub kategori (akidah, syari’ah, dan akhlak) ialah iman kepada Allah, Iman kepada Nabi, Iman kepada Kitab, ibadah, muamalah, akhlak kepada sesama, dan akhlak kepada lingkungan.